Development of the Sokółka district for bicycle tourism - Oniszczuk, Natalia (Turystyka i krajoznawstwo, 2021)
The purpose of the article is to propose changes in the development of the Sokółka district for bicycle tourism based on data obtained at the beginning of 2020. A field reconnaissance was carried out, and the materials collected and information found on the poviat’s websites were analyzed. A SWOT analysis was prepared in terms of bicycle tourism and, as part of the work, several maps were created through the QGIS program showing both tourist attractions in the Sokółka district and bicycle routes. On the basis of the information obtained, several changes were proposed in order to create places of interest for bicycle tourists in the studied area. A map of potential stopping points for cyclists was also produced and several ideas were proposed to improve the promotion of the area.